Education on The Production of Botanical Pesticides from Papaya Leaves (Carica papaya L.) in Baru Ilir West Balikpapan: Edukasi Pembuatan Biopestisida Tumbuhan dari Daun Pepaya (Carica papaya L.) di Baru Ilir Balikpapan Barat - Fatma Putri Salsabillah; Trideli Lumban Gaol; Iskandar Muda (ANDIL Mulawarman Journal of Community Engagement, 2026)
The periodic use of chemical-based pesticides in large quantities in agricultural practices can have adverse effects on the environment, human health, and ecosystem sustainability. Therefore, environmentally friendly and applicable alternatives are needed, one of which is the use of plant-based pesticides such as papaya leaves (Carica papaya L.), which are rich in bioactive compounds including papain, saponins, flavonoids, and alkaloids. This community service activity provided education on the preparation of plant-based pesticides from papaya leaves and was conducted in Baru Ilir Subdistrict, West Balikpapan. The aim of the activity was to improve farmers’ knowledge, skills, and awareness regarding the importance of sustainable pest management. The method employed was conceptual education through counseling sessions. The results showed that participants gained new understanding (soft skills) regarding the benefits of botanical pesticides, along with improved practical skills (hard skills) in preparing pesticide solutions from papaya leaves (Carica papaya L.). In addition, participants expressed an interest in reducing their dependence on chemical pesticides and began applying botanical pesticides to their crops. This activity is expected to serve as an initial step toward the implementation of environmentally friendly and sustainable agriculture in Baru Ilir Subdistrict, West Balikpapan.